Trophotagma Enrichment Axes in Poaceae - Muchut, Sebastián Elías; Pilatti, Vanesa; Uberti Manassero, Nora Graciela; Perreta, Mariel Gladis; Vegetti, Abelardo Carlos (2018)
This review is intended: (1) to interpret and characterize morphological variations observed in the structure of the enrichment axes, located below the terminal inflorescence in Poaceae; and (2) to study the relationship between the intensity of development of such axes and the size of terminal inflorescence. An important reduction in the development of the terminal inflorescence is generally accompanied by a significant development of enrichment axes. It is necessary to adequately characterize these enrichment axes, differentiating them from the terminal inflorescence. Since the intensive development of enrichment axes in synflorescences of many grass genera has caused misinterpretations of the inflorescence structure, to include them as parts of the terminal inflorescence.